Effect of Different Nitrogen Concentrations on the Growth Rate of Caulerpa lentillifera Sea Grapes - Amanda, Rofifah Aulia; Mukhlis, Alis; Lumbessy , Salnida Yuniarti (Jurnal Biologi Tropis, 2025)
Caulerpa lentillifera is a strategic macroalgae commodity in controlled cultivation that requires nutrient management optimization for maximum productivity. This study evaluated the effect of nitrogen concentration variations (0, 15, 30, 45 ppm) on algae growth parameters in a complete randomized design with three replicates over 15 days (12 experimental units). Data analysis was carried out using One-Way ANOVA (95% confidence level) and Duncan post-hoc test to compare parameters such as absolute and relative biomass, specific growth rate, rate of decline, biomass residue, and chlorophyll-a content. The results showed that the concentration of 45 ppm resulted in the highest absolute biomass (23 g) and optimal relative growth (36.59%), while 30 ppm provided the highest specific growth rate (7.40 %/day) and the lowest specific decline rate (2.3 %/day). Surprisingly, the control (0 ppm) recorded the highest chlorophyll-a (20 μg/g), while at 45 ppm there was a significant decrease (9.67 μg/g). It is concluded that the optimal nitrogen range is 15–30 ppm, as it offers the best balance between productivity and physiological stability. At the applicative level, it is recommended the use of moderate nitrogen concentrations in commercial cultivation of C. lentillifera for economic efficiency without sacrificing biomass quality.